1996
DOI: 10.1111/1523-1747.ep12294284
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasin: A Novel Chemotactic Protein

Abstract: Inflammatory skin disorders such as psoriasis show a preferential epidermal infiltration of neutrophils and T lymphocytes. This observation raises a question as to which factors determine the appearance and composition of leukocyte tissue infiltrations. Previously, we described a low molecular mass calcium-binding protein (psoriasin, molecular mass 11,457 Da, pI 6.77) belonging to the S1OO family that is highly upregulated in psoriatic keratinocytes and whose expression patterns implied a role in the inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(177 citation statements)
references
References 40 publications
6
169
0
2
Order By: Relevance
“…6). S100 family members have also been demonstrated to be involved in the response to infection (51)(52)(53). In addition to S100A7, S100A8, and S100A9, which were previously reported to be up-regulated by IL-22 (13,14), we found that S100A12 and S100A15 were strongly induced by the IL-20 subfamily of cytokines (supplemental Table I and Fig.…”
Section: Unique Gene Signatures Induced By Il-20 Subfamily Cytokines supporting
confidence: 63%
See 1 more Smart Citation
“…6). S100 family members have also been demonstrated to be involved in the response to infection (51)(52)(53). In addition to S100A7, S100A8, and S100A9, which were previously reported to be up-regulated by IL-22 (13,14), we found that S100A12 and S100A15 were strongly induced by the IL-20 subfamily of cytokines (supplemental Table I and Fig.…”
Section: Unique Gene Signatures Induced By Il-20 Subfamily Cytokines supporting
confidence: 63%
“…S100 family proteins were some of the most highly up-regulated genes in our microarrays and as determined by quantitative RT-PCR. Proteins of this family, whose genes are found in the epidermal differentiation complex, are calcium-binding proteins that are associated with inflammation, some of which have been shown to have chemotactic and direct antimicrobial activities (51)(52)(53). Other genes induced by the IL-20 subfamily cytokines and also in psoriatic skin include chemokines, angiogenic factors, tissue kallikreins, and ␤-defensins (38,48,49,71).…”
Section: Discussionmentioning
confidence: 99%
“…Discussion S100A7 is commonly upregulated in breast cancer, most frequently in ductal carcinoma in situ with a high grade, ER-negative phenotype (Emberley et al, 2004a, b). The frequent association of inflammation with this tumor phenotype supports the view that S100A7 may be a chemotactic factor for inflammatory cells (Jinquan et al, 1996;Wolf et al, 2008), although it is also possible that inflammation may precede and stimulate S100A7. We have shown here that two IL-6 family cytokines, OSM and IL-6, regulate S100A7 in breast cell lines via (in MCF7 cells) PI3K, ERK1/2 and STAT3 signaling.…”
Section: Inflammatory Cytokines Induce S100a7 Expression In Breast Cellssupporting
confidence: 56%
“…In fact, S100A7 has been identified in unbiased studies of mRNA and protein expression as amongst the most highly expressed genes in certain subsets of breast tumours (Leygue et al 1996, Al-Haddad et al 1999, Emberley et al 2003. Some of its effects are mediated by intracellular interaction with JAB1 (Emberley et al 2003, but S100A7 is also secreted and has chemotactic effects on inflammatory cells (Jinquan et al 1996). Indeed, the mouse S100A7 homologue recruits tumour-associated macrophages in a murine orthotopic breast cancer model (Nasser et al 2012).…”
Section: Cd68mentioning
confidence: 99%